An atypical BAR domain protein in autophagy. Issue 7 (3rd July 2018) - Popelka, Hana; Klionsky, Daniel J.; Ragusa, Michael J.
ABSTRACT: The sorting nexin Atg20 interacts with the selective macroautophagy/autophagy scaffolding protein Atg11, suggesting an important role for Atg20 in the initiation of selective autophagy. To explore this possibility, we recently investigated the structure and function of Atg20 using a variety of biophysical and yeast genetic approaches. Our data demonstrate that the BAR domain of Atg20 interacts with Snx4/Atg24 to form an asymmetric heterodimeric BAR domain complex. Atg20 also contains a long intrinsically disordered N terminus that facilitates binding to Atg11 and a large 89-amino acid insertion in its BAR domain, which we have termed the BAR-GAP. This BAR-GAP region is a unique feature of Atg20 and has not been observed in other BAR domains. Furthermore, the BAR-GAP of Atg20 contains an amphipathic helix which is required for membrane binding, tubulation and autophagy. Our findings demonstrate the important role of this novel region in autophagy.